Excessive progesterone impairs mouse decidualization via the Kyn-AhR pathway - Luo, Hui-Na; Yang, Hong-Yuan; Wang, Zai-Mei; Luo, Jia-Mei; Zhang, Tong-Tong; Yang, Zeng-Ming (Frontiers in Cell and Developmental Biology, 2025)
Progesterone (P4) is essential for pregnancy establishment and maintenance. Clinically, P4 is widely used to regulate the menstrual cycle, maintain pregnancy, and treat luteal phase deficiency. However, P4 administration protocols, particularly regarding routes, dosage, and timing remain poorly defined. Although excessive P4 impairs embryo implantation and decidualization in mice, the underlying mechanism remains unclear. Our data show that decidualization in day 8 pregnant mice and artificial decidualization in day 8 pseudopregnant mice are impaired by 4 mg or 8 mg/mouse P4. The mRNA levels of Prl8a2 and Prl3c1, markers of in vitro decidualization are significantly downregulated by 10 or 20 μM P4. The uterine fluorescent signal of indoleamine 2,3-dioxygenase 1 (IDO1) and protein levels of tryptophan 2,3-dioxygenase (TDO) are increased after ovariectomized mice are treated with excessive P4. Treatment of uterine stromal cells with excessive P4 also significantly upregulates the protein levels of IDO1 and TDO, and kynurenine (Kyn) secretion. Epacadostat (IDO1 antagonist) or RU486 (progesterone receptor antagonist) effectively block P4-induced Kyn elevation. The mRNA levels of Prl8a2 and Prl3c1 and the protein levels of BMP2 are significantly inhibited by Kyn. The high-dose of P4 activates the aryl hydrocarbon receptor (AhR) and its downstream targets CYP1A1 and CYP1B1. Under in vitro decidualization, the mRNA levels of Prl8a2 and Prl3c1 are inhibited by 2-OH-E2 and 4-OH-E2, the catalytic products of CYP1A1 and CYP1B1, respectively. CH-223191, a specific AhR antagonist, effectively counteracts the effects of Kyn on Cyp1a1, Cyp1b1, and Prl8a2 expression. Additionally, nucleolar size in stromal cells is increased both in vivo and in vitro following excessive P4 treatment. Our findings suggest that excessive P4 impairs mouse decidualization via the Kyn-AhR pathway.